2019
DOI: 10.1111/jfd.13060
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal effects of common disinfectants against tilapia lake virus

Abstract: Tilapia lake virus (TiLV) is an emerging virus associated with high fish mortality and economic losses. This study investigates the virucidal effects of the following disinfectants (active ingredients) on TiLV: 2.5 ppm iodine, 10 ppm sodium hypochlorite (NaOCl), 300 ppm hydrogen peroxide (H2O2), 80 ppm formalin and 5,000 ppm (0.5%) Virkon®. Factors that affect the disinfectants’ efficacy, including temperature, contact time and soiling (organic matter) interference, were examined under conditions mimicking nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…While formalin at 80 ppm required a longer incubation of 60 min at 28°C for complete inactivation. However, NaOCl, iodine and H 2 O 2 showed reduced efficacy when the level of synthetic organic matter present in the water was increased to mimic soiling interference (Jaemwimol, Sirikanchana, Tattiyapong, Mongkolsuk, & Surachetpong, 2019). Another study has also shown that TiLV is susceptible to buffered povidone–iodine complex and chlorine (Soto, Yun, & Surachetpong, 2019).…”
Section: Tilv Disease Control and Preventionmentioning
confidence: 99%
“…While formalin at 80 ppm required a longer incubation of 60 min at 28°C for complete inactivation. However, NaOCl, iodine and H 2 O 2 showed reduced efficacy when the level of synthetic organic matter present in the water was increased to mimic soiling interference (Jaemwimol, Sirikanchana, Tattiyapong, Mongkolsuk, & Surachetpong, 2019). Another study has also shown that TiLV is susceptible to buffered povidone–iodine complex and chlorine (Soto, Yun, & Surachetpong, 2019).…”
Section: Tilv Disease Control and Preventionmentioning
confidence: 99%
“…Alternatively, the application of disinfectants to treat water should be applied to prevent the risk of TiLV contamination. Recent studies showed that the most common disinfectants are very effective in inhibiting TiLV (Jaemwimol et al., 2019; Soto et al., 2019). Importantly, a basic knowledge of how the virus spreads in the fish population is required to minimize outbreaks or control the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Disinfectants should be safe for use around aquaculture systems and sufficient to kill pathogenic agents of concern on the farm. Commonly used disinfectants include iodophors (e.g., Wescodyne, Betadine) and Virkon Aquatic, which are effective against most aquatic bacterial and viral pathogens affecting tilapia 102 . Strict security should also be enforced at both in‐land and cage culture systems to restrict the movement of visitors and ensure compliance with biosecurity protocols 18…”
Section: Implementing Biosecurity Measures In the Value Chainmentioning
confidence: 99%